A Bio-Crypto Protocol for Password Protection Using ECC - Srinivasan Nagaraj; G.V.S.P. Raju; G Apparao; B. Kishore (Bulletin of Electrical Engineering and Informatics, 2015)
In  information  security the  following security parameters like, integrity , non repudiation and confidentiality , authentication   must be satisfied.  To avoid thievery of organization resources  it needs be secured in more efficient way  and there is always demand  for different levels of security attacks include virus , brute force and Eveadroper  in business that  organizations make use of voice biometrics an attractive low-cost. Voice biometrics is the  cheapest  among the  other biometrics and used all levels for management to buy readily available metric and it is the way of  identifying individuals remotely  with high level of accuracy . In this work, we have been designed a  new  password- authentication approach  that provides security  using voice biometrics for authentication and uses the device  itself into an authenticator which uses  voice itself as its passwords and we are primarily interested in keys that can be temporally reproduced on the same device from the same user’s voice. Public and private keys are generated  randomly from the user's voice  and stored in the voice file(.wav).This Method uses voice recognition , include the operation of  register( recording feature ) or voice prints  and  storing of one or more voice passwords into the  database. It uses ECDSA to perform the authentication process that matching the  voice sample  with the database. The recognition, entity makes the database  to decide that  the sample is matched to perform an operation or not. Our proposed approach  generates cryptographic keys from voice input itself and this algorithm developed an adhoc basis. It can effectively defend  attacks specially brute force attack in system networks.